Delineation of chicken immune markers in the era of omics and multicolor flow cytometry - Härtle, Sonja; Sutton, Kate; Vervelde, Lonneke; Dalgaard, Tina S. (Frontiers in Veterinary Science, 2024)
Multiparameter flow cytometry is a routine method in immunological studies incorporated in biomedical, veterinary, agricultural and wildlife research, and routinely used in veterinary clinical laboratories. Its use in diagnostics of poultry diseases is still limited, but due to the continuous expansion of reagents and cost reductions, this may change in the near future. Although the structure and function of the avian immune system shows commonalities with mammals, at the molecular level there is often low homology across species. Cross-reactivity of mammalian immunological reagents is therefore low, but nevertheless the list of reagents to study chicken immune cells is increasing. Recent improvement in multicolor antibody panels for chicken cells has resulted in more detailed analysis by flow cytometry and has allowed the discovery of novel leukocyte cell subpopulations. In this paper we present an overview of the reagents and guidance to perform multicolour flow cytometry using chicken samples and common pitfalls to avoid.